Beyond the Left-Right Spectrum: A Typological Analysis of Ideologues in China's Weibo Space. Issue 119 (3rd September 2019) - Huang, Ronggui; Gui, Yong; Sun, Xiaoyi
ABSTRACT: This study aims to investigate Weibo users' political ideologies in China. It argues that a left-right spectrum cannot adequately depict the ideological landscape, and proposes a typological framework to guide the analysis of competing ideologies. Based on a sample of 3440 Weibo users, this article uses latent class model to identify sub-types of ideologues. It discerns five ideological groups, namely Maoists, regime defenders, full-fledged liberals, economic liberals, and political liberals, as well as one politically silent group. The results show that liberal leaning Weibo users are not a homogeneous group, and should not be holistically conceived as regime challengers in opposition to regime defenders. To a certain degree, economic liberals are more similar to regime defenders than Maoists, and this can be better understood from a typological perspective than a spectrum perspective. This article concludes with a discussion on the political implications of the findings.